Redesign methodology for cost effective assembly of aerospace structures - El-Nounu, AbdulRahman (2018)
The research addresses the topic of design for assembly from an aerospace structures perspective. Aerospace assembly has traditionally taken secondary important to aircraft performance. This approach has been validated through healthy sales, most recently demonstrated in the Single Aisle market. However, in recent times, design for assembly has become more important. There are two main drivers behind this shift in focus. The first is a desire from aircraft manufacturers to maximise profits on existing aircraft orders through redesign. The second is the future outlook of aircraft sales, estimated to be in the trillions of dollars 2035. Aircraft manufacturers have therefore recognised that optimising their manufacturing system is critical lest market share is lost to emerging aircraft manufacturers through an inability to meet rising demand. Three methods are then developed to provide design for assembly indicators for development decisions. The underpinning methodology behind these methods is a data driven approach. This is that cost saving decisions can be made using the mass of existing available data from production systems at early stages provided that key indicators are identified. The methods allow engineers to make informed decisions on design for assembly and technology development. The first method addresses the issue of redesign. A tool is presented that relies on available data of assembly processes to make recommendations on redesign projects. The method is populated with real data and its output is compared against real business decisions. The results show that the method provides positive direction and is beneficial when filtering between costly redesign projects. The second method addresses design for assembly at early product development. A complexity metric is developed using a combination of historical data and known data at a particular development stage to produce a complexity metric that carries out an analysis of a full assembly system. It provides the engineer with a macro view enabling the identification of potential bottlenecks. Data from a previous product was used to demonstrate this method. The results shown were able to highlight real issues and make recommendations about technology strategy. The final method developed in this research recognised that design for assembly and assembly technology were synergetic and should be developed together. It proposed an assembly process characterisation technique to enable future technology strategy planning at design for assembly stage. The tool was demonstrated using existing data and proposed several concepts for a future product to enable higher levels of automation and more cost effective future technology implementation. The research concluded that there was a definite advantage in using the demonstrated methods in providing direction to an aircraft manufacturing business. In the redesign method and the complexity analysis method this was validated through comparison against real business decisions. The two methods were in line with business thinking. Also, where the redesign method was different in its advice compared with business direction, it was shown that following the advice of the method would have been beneficial to the business. It was more difficult to validate the shared platform approach method due to its results providing indicators for future decisions. Early analysis into its potential validity through technology benchmarking looked promising.